Penggunaan Fitur Bahasa Perempuan pada Novel Tempurung Karya Oka Rusmini - Ni Nyoman Astrini Utami (Diglosia: Jurnal Kajian Bahasa, Sastra, dan Pengajarannya, 2022)
The use of women's language with a Balinese cultural background with a patriarchal culture is interesting to analyze. The novel 'Tempurung' by Oka Rusmini tells the story of women with Balinese cultural backgrounds. There are sixteen female characters in this novel, while three are male characters. This study analyzes the features of women's language used by female characters, which are analyzed using the referential, pragmatic, and distribution methods. Based on the results of the analysis, female characters use eight out of ten features of the female language, namely intensifier (40.72%), empty adjectives (17.01%), tag questions (16.49%), super polite form (7.22%), rising intonation on declarative (6.70%), hypercorrect grammar (6.70%), emphatic stress (3.09%), and lexical hedges or fillers (2.06%). Avoid strong swear words, and female characters do not apply precise colour terms. Female characters' use of women's language features is motivated by a patriarchal culture that makes men superior while women are inferior. The caste system in Balinese culture also underlies the use of female language features by female characters, for example, using polite forms when speaking with interlocutors who have a higher caste.